2014
DOI: 10.1186/1478-7547-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Changes in costs and effects after the implementation of disease management programs in the Netherlands: variability and determinants

Abstract: ObjectivesThe aim of the study was to investigate the changes in costs and outcomes after the implementation of various disease management programs (DMPs), to identify their potential determinants, and to compare the costs and outcomes of different DMPs.MethodsWe investigated the 1-year changes in costs and effects of 1,322 patients in 16 DMPs for cardiovascular risk (CVR), chronic obstructive pulmonary disease (COPD), and diabetes mellitus (DMII) in the Netherlands. We also explored the within-DMP predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Our study does not determine the pathway through which total daily admissions mediate its effect on readmissions, the most likely hypothesis is that it reflects overstretching of physicians during the crucial early hours of an admission leading to an avoidable reduction in the quality of care provided. However, while chronic disease management programmes may be cost effective and reduce readmission rates, the load on the hospital with its capacity constraints would all require extra resources from the public purse in an era of austerity [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Our study does not determine the pathway through which total daily admissions mediate its effect on readmissions, the most likely hypothesis is that it reflects overstretching of physicians during the crucial early hours of an admission leading to an avoidable reduction in the quality of care provided. However, while chronic disease management programmes may be cost effective and reduce readmission rates, the load on the hospital with its capacity constraints would all require extra resources from the public purse in an era of austerity [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect is the economies of scale, ie, costs per patient reduce when using facilities for a larger target group. 15 …”
Section: Development Of a Diagnostic Pathwaymentioning
confidence: 99%
“…Tsiachristas et al investigated the changes in cost-effectiveness in 1322 patients treated in 16 different disease management plans. These authors observed that physical activity (21%) in COPD patients had a significant positive effect on costeffectiveness [41].…”
Section: Discussionmentioning
confidence: 91%